Evaluation of Financial Management of Santri Pondok Pesantren API Syubbanul Wathon Tegalrejo Secang Through the SIMKEU Application - Nala Khilmi Rosyidah; Milna Wafirah; Siswanto Siswanto (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: The implementation of the SIMKEU application at API Syubbanul Wathon Tegalrejo Secang Islamic Boarding School has become the primary focus in inhancing institutional financial management. This research aims to evaluate the application’s implementation through a qualitative case study approach. The results revealed several issues encountered, such as data entry errors, feature limitations, and a lack of system updates. Thematic analysis methods were used to identify key themes emerging from interview data, observation, and document analysis. These findings provide insight into the challenges and solutions associated with implementing SIMKEU in educational settings. Recommendations for improvement include intensive user training, more frequent system updates, and the development of new features to enhance the efficiency and effectiveness of financial management in Islamic boarding schools. With the implementation of these recommendations is expected to improve the quality of financial management and educational services at API Syubbanul Wathon Islamic Boarding School. Keywords: Islamic Boarding School, SIMKEU, Financial Management, Evaluation